2020
DOI: 10.1109/tvcg.2019.2934283
|View full text |Cite
|
Sign up to set email alerts
|

What is Interaction for Data Visualization?

Abstract: Interaction is fundamental to data visualization, but what "interaction" means in the context of visualization is ambiguous and confusing. We argue that this confusion is due to a lack of consensual definition. To tackle this problem, we start by synthesizing an inclusive view of interaction in the visualization community-including insights from information visualization, visual analytics and scientific visualization, as well as the input of both senior and junior visualization researchers. Once this view take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 106 publications
0
37
0
1
Order By: Relevance
“…Both survey and interviews suggested that decision makers lack "decision making" tools designed to support the flow along all decision phases: INTELLIGENCE Fig. 3: Taxonomy of allowable user actions in a visualization system [71]. Increasing the cardinality of such actions increases the degree of flexibility of the system.…”
Section: Future Visualization Toolsmentioning
confidence: 99%
“…Both survey and interviews suggested that decision makers lack "decision making" tools designed to support the flow along all decision phases: INTELLIGENCE Fig. 3: Taxonomy of allowable user actions in a visualization system [71]. Increasing the cardinality of such actions increases the degree of flexibility of the system.…”
Section: Future Visualization Toolsmentioning
confidence: 99%
“…where MaxAge is the maximum age of infected people. Visual representation of such a value by conventional methods (graphs, charts, tables) is quite problematic as the number of components is high (in the extreme case age can be a continuous value) [20,21]. Very often, to analyze and interpret such data, rounding the parameter and switching to certain ranges are used.…”
Section: Methods Generalisation For Continuous Datamentioning
confidence: 99%
“…Although interaction is commonly used in data visualization, efforts to define interactivity are ongoing [10]. Additionally, there is no consensus on the best visualization for Bayesian reasoning [23,29,32].…”
Section: Methodsmentioning
confidence: 99%
“…Recent work by Dimara and Perin [10] defines interaction (in visualization) as "the interplay between a person and a data interface involving a data-related intent, at least one action from the person and an interface reaction that is perceived as such." Similarly, Yi et al [45] and Heer and Shneiderman [21] construct taxonomies of interactions for visualization.…”
Section: Value Add Of Interactionmentioning
confidence: 99%
See 1 more Smart Citation